Is there a Moral Right to Vote? - Beckman, Ludvig (Ethical theory and moral practice, 2017)
The question raised in this paper is whether legal rights to vote are also moral rights to vote. The challenge to the justification of a moral right to vote is that it is not clear that the vote is instrumental to the preservation of some critical interest of the voter. Because a single vote has no impact on electoral outcomes, the right to vote is unlikely to serve the interests of the individual. The account developed in this paper holds that moral voting rights can be justified once we acknowledge that voting by a sub-set of citizens is among the necessary preconditions for democratic institutions making a significant difference to their collective interests. The justification of a moral right to vote does not, then, apply to each individual citizen but only to a sub-set of them. In order to justify inclusive moral voting rights, the further consideration must be added that individuals have critical interests in public recognition of equal status. An inclusive moral right to vote accordingly depends on both collective interest in the outcomes of democratic institutions and on individual interest in equal recognition.